2017
DOI: 10.1002/advs.201700528
|View full text |Cite
|
Sign up to set email alerts
|

A Pickering Emulsion Route to Swimming Active Janus Colloids

Abstract: The field of active colloids is attracting significant interest to both enable applications and allow investigations of new collective colloidal phenomena. One convenient active colloidal system that has been much studied is spherical Janus particles, where a hemispherical coating of platinum decomposes hydrogen peroxide to produce rapid motion. However, at present producing these active colloids relies on a physical vapor deposition (PVD) process, which is difficult to scale and requires access to expensive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
64
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 44 publications
1
64
1
Order By: Relevance
“…There are a few papers that show the influence of interface nanostructure on the motion of the catalytic nano/micromotors . The mesoporous structure together with the interfaces has even been lesser addressed for the case of light‐driven micromotors, which should play the dominant role on the self‐propulsion .…”
Section: Introductionmentioning
confidence: 99%
“…There are a few papers that show the influence of interface nanostructure on the motion of the catalytic nano/micromotors . The mesoporous structure together with the interfaces has even been lesser addressed for the case of light‐driven micromotors, which should play the dominant role on the self‐propulsion .…”
Section: Introductionmentioning
confidence: 99%
“…[30] It was recently found that such a change in chemistry also affects oxides, materials usually considered quite stable under electron beam irradiation. [31] This destabilizing effect is also seen for amorphous SiO 2 , an important oxide in many nanoscale applications, [32][33][34] which although stable in vacuum, is severely destabilized by electron beam induced chemistry in water. [35,36] Specifically, it was shown that upon imaging with a scanning electron beam, silica nanospheres tended to elongate in the scanning direction of the beam and shrink significantly over time.…”
mentioning
confidence: 99%
“…The scalability is a property hard to fulfill for the planar‐based techniques (rolled‐up planar nanolayers, electrochemical template pore deposition). The answer to the problem is approached by wet‐chemical synthesis of micro/nanoparticles directly in solution, where the primary challenge is to introduce a highly asymmetrical component into the particle, to use it for directional self‐propulsion …”
Section: Introductionmentioning
confidence: 99%